The Hermeneutic Thoughts of Ashgar Ali Engineer in The Interpretation of Feminism - Irsyadunnas Irsyadunnas (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Using hermeneutic as a method and approach in systematic interpretation of Al-Qur'an had begun during contemporary period. The reality and fulfillment of the academic standard had pushed contemporary Muslim scholars used the method. Asghar Ali Engineer was one of the Muslim scholars who supported hermeneutic in the study of Qur'anic exegesis on feminism. This article examined the impacts on how feminism in Engineer's hermeneutic exegesis of the Qur'an played significant role in the Qur'anic exegesis studies. He was placed at the same position with other contemporary Muslim scholars. His popularity as a Muslim feminist had been well-known mainly on his interpretation of the Qur'an about feminism. According to Engineer, the interpretation of the Qur'an had to consider three concepts, “the freedom of Al-Qur'an,” “the spirit of the Qur'an against Patriarchy,” and “the classified Qur'anic verses and sociological normative.” Engineer offered three sources when interpreting al- Qur'an; namely, text, context, and perspective. The Engineer interpreted Qur'anic verses about gender at QS. An-Nisa: 1; 3, and 34 by applying these concept, method and sources